An Educational Program to Address Maternal Health Disparities and High Infant Mortality in North Carolina [7M]. (May 2018) - Patel, Reena; Jones, Rebecca; Sutton, Jill
Abstract : INTRODUCTION: Infant mortality remains of significant concern in the United States. North Carolina infant mortality rates surpass national averages, while Pitt County exceeds the state average. Various factors have been shown to impact infant mortality, including prenatal care, breastfeeding, and socioeconomic status. Prenatal support and education can have an advantageous effect, particularly for vulnerable populations. This project seeks to demonstrate positive effects of prenatal support and education on anxiety, confidence, and lifestyle for mothers and partners in Pitt County, as analyzed through longitudinal prenatal education. METHODS: A curriculum was developed to cover topics including pregnancy health, breastfeeding, infant care, and safety. Participants completed pre- and post-class surveys, including the Spielberger State-Trait Anxiety Inventory, Lifestyle Indicator Questionnaire (Godwin), and skill confidence assessments. These items were scored and analyzed. RESULTS: The data indicated a decrease in mean anxiety from pre- to post-class (pre-class score: 33.8 vs. post-class score: 27.9; P<0.001). The data also showed increased mean confidence scores in multiple areas: breastfeeding from 1.9 to 2.9, infant CPR from 1.7 to 3.6, and infant choking rescue from 1.8 to 3.7 (P<0.001). Corresponding infant CPR and rescue assessment scores increased from a mean of 44.0 % to 98.0% (P<0.001). In qualitative analysis, 11 individuals reported specific healthy lifestyle changes throughout the series. CONCLUSION: This data suggests that prenatal support and education can decrease anxiety, increase confidence, and contribute to beneficial lifestyle changes, which can assist in decreasing infant mortality. Future research will further investigate longitudinal data to better understand program benefits and adapt strategies to improve effects.